PELATIHAN MANAJEMEN LABORATORIUM TERPADU BAGI GURU SDN KEPUH KIRIMAN SIDOARJO - Imas Srinana Wardani; Triman Juniarso; Reza Rachmadtullah; Apri Irianto; Wahyu Susiloningsih (LPPM Universitas Bina Bangsa, 2022)
This training aims to provide understanding and motivation to the importance of integrated laboratory management. The participants in this training are teachers from SDN Kepuh Kiriman Sidoarjo. The training methods carried out are lectures, modeling, and workshops. Lectures are carried out by presenting material and workshops are carried out by means of assistance during group work. The result of the training activity was that teachers of SDN Kepuh Kiriman Sidoarjo gained knowledge about integrated laboratory management and how to implement this knowledge in schools so that the quality and quantity of laboratories in schools became better and more effective